Chapter Il video a 360° come supporto didattico. Un caso di studio nell'insegnamento di Analisi Sensoriale degli Alimenti - MONTELEONE, ERMINIO (Studi e saggi, 2022)
The chapter presents a case study based on the design, development, and testing of an interactive 360° video applied to the teaching of Sensory Analysis of Food at the University of Florence. The case study describes the design of 360° video storyboards and the creation of the video by the use of 360° cameras for reproducing a sensory laboratory environment. Video enrichment with Vivista, an educational software allowing lecturers to embed interaction points (e.g. quizzes, texts, images) within the 360° videos is also described. Different immersive modalities for the use of the videos with students in different contexts are described and discussed. The chapter concludes with a reflection on the opportunities that 360° videos may provide to university students for practice and experience.